2004
DOI: 10.1021/cm0489284
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of VUV Damage in BaMgAl10O17:Eu2+

Abstract: We have studied vacuum ultraviolet (VUV)-induced damage processes in BaMgAl 10 O 17 : Eu 2+ using a unique accelerated life-testing device. Emission, excitation, and reflectance spectra of doped and undoped samples before and after VUV damage reveal two independent mechanisms of degradation. The observed color shift in damaged materials is due to the migration of Eu 2+ ions to metastable sites in the lattice. The observed loss of brightness is due in part to the formation of color centers in the spinel layer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 25 publications
3
55
0
Order By: Relevance
“…The excitation spectra had a broad in the region of 180-260 nm which should be the two bands overlapped because of the non-symmetry shape of the excitation band in the spectrum. The one would be attributed to the Ba-O absorption because the many former reports about BAM:Eu 2+ have identified that Ba-O absorption band is about 180 nm [31][32][33]. Except the BAM, the absorption band of Ba-O was also reported in the Ba 2 SnO 4 :Eu 3+ [17].…”
Section: Resultsmentioning
confidence: 90%
“…The excitation spectra had a broad in the region of 180-260 nm which should be the two bands overlapped because of the non-symmetry shape of the excitation band in the spectrum. The one would be attributed to the Ba-O absorption because the many former reports about BAM:Eu 2+ have identified that Ba-O absorption band is about 180 nm [31][32][33]. Except the BAM, the absorption band of Ba-O was also reported in the Ba 2 SnO 4 :Eu 3+ [17].…”
Section: Resultsmentioning
confidence: 90%
“…The degradation of BAM sample decreases emission efficiency, shifts emission peaks, increases FWHM and shifts chromaticity coordinates. The mechanism of degradation has been discussed frequently [11][12][13][14]. Part of decrease in intensity is due to precipitation as EuMgAl 11 O 19 [7].…”
Section: Blue Phosphorsmentioning
confidence: 99%
“…Moreover, VUV irradiation produces colour centres having an absorption band at 235 nm. This absorption disrupts the radiative energy-transfer mechanism thus decreasing the emission efficiency [13].…”
Section: Blue Phosphorsmentioning
confidence: 99%
“…When Eu 2+ is substituted into the host lattice, it can have been three possible locations: Beevers-Ross (BR), anti-BeeversRoss (a-BR), and mid-oxygen (mO) sites in the mirror plane [7]. Peak fitting results show that the primary emission center is assigned to Eu 2+ on the normal Ba site (the BR site in the cation layer), while the second center is assigned to Eu 2+ on the a-BR site.…”
Section: Introductionmentioning
confidence: 99%
“…Peak fitting results show that the primary emission center is assigned to Eu 2+ on the normal Ba site (the BR site in the cation layer), while the second center is assigned to Eu 2+ on the a-BR site. The third center has been assigned alternatively to Eu 2+ in the spinel block, to Eu 2+ on the mid-oxygen sites in the cation layer, or to Eu 2+ associated with defect center in the lattice, But it is not populated in the fresh samples [7]. On the mechanism of the deterioration, much research has been conducted.…”
Section: Introductionmentioning
confidence: 99%